Rethinking Profit and Loss Sharing: Regulatory Paradoxes in Mudharabah Savings and the Operationalization of Maqasid al-Shariah - Irma Novida; Junarti Junarti; Hidayatulloh; Nur Hidayah; Ujang Maman (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This article examines the regulatory paradox in the governance of mudharabah savings in Indonesian Islamic banking, where the principle of profit-and-loss sharing (PLS), which is doctrinally based on risk sharing, operates within a regulatory architecture oriented towards risk control and depositor protection. The interaction between risk sharing based contractual rationality and risk containment based prudential regimes raises structural questions about whether PLS still functions as a substantive governance paradigm, or primarily as a formal legal category in a stability oriented financial regime. This study aims to identify the mudharabah regulatory framework and analyze it through the principle of hifz mal in maqasid sharia as a systemic evaluation instrument for consistency between the normative objectives of Islamic finance and its supervisory mechanisms. The study uses a normative-empirical legal design. The primary data consists of the Law on Islamic Banking, Financial Services Authority (OJK) regulations, and fatwas from the National Sharia Council Indonesian Ulema Council (MUI) regarding mudharabah contracts. The secondary data includes academic literature on PLS and maqasid al-sharia. Data were collected through documentation studies and analyzed using content analysis techniques. The findings show that the integration of PLS into the modern prudential regime produces three interrelated paradoxes moderation of risk transmission through risk control mechanisms, structural limitation of depositor exposure to losses through deposit insurance, and stabilization of returns due to competitive benchmarking pressures. Furthermore, this article shows that in its interaction with the modern regulatory regime, the principle of hifz mal in maqasid sharia has undergone a transformation from a normative doctrine to an analytical instrument for reassessing PLS governance. This process leads to the repositioning of PLS from mere regulatory compliance to a maqasid oriented governance framework that allows for critical evaluation of stability orientation, risk distribution fairness, and systemic integrity. The main contribution of this research lies in the operationalization of maqasid sharia as a methodological framework for re-reading PLS governance, while offering a conceptual reconstruction of the relationship between the principles of risk sharing and modern financial stability.